Adobe After Effects CS5 learn by video - Taylor, Angie; Kopriva, Todd.; Safari eBooks ([S.l.] : Video2brain, 2010)
"This innovative product from Adobe Press combines an incredible 14 hours of high-quality HD video training and a full-color printed reference to teach the fundamentals of After Effects CS5. Experienced instructor Angie Taylor and Adobe Technical Support Lead Todd Kopriva present the video instruction, complete with lesson files, assessment quizzes and review materials. The video is wrapped in a unique interface that allows the viewer to jump to any topic and also bookmark individual sections for later review. The unique Watch-and-Work mode shrinks the video into a small window to allow the student to work alongside in After Effects. Project files used in the lessons allow viewers practice what they've learned, and interactive review questions help reinforce freshly gained knowledge."--Resource description page.
Title from resource description page (viewed Feb. 24, 2011).
Keywords: Adobe After Effects; Image processing -- Digital techniques; Cinematography -- Special effects -- Data processing; Electronic books